2000
DOI: 10.1095/biolreprod63.1.242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Porcine Oviduct-Specific Glycoprotein on Fertilization, Polyspermy, and Embryonic Development In Vitro1

Abstract: This study evaluated the effects of porcine oviduct-specific glycoprotein (pOSP) on in vitro fertilization (IVF), polyspermy, and development to blastocyst. Experiment 1 evaluated the effects of various concentrations (0-100 microgram/ml) of purified pOSP on fertilization parameters, including penetration, polyspermy, male pronuclear formation, and mean number of sperm penetrated per oocyte. Experiment 2 examined the ability of an anti-pOSP immunoglobulin G to inhibit the observed effects of pOSP on fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 54 publications
3
84
0
2
Order By: Relevance
“…cycle, (ii) nucleotide and amino acid sequences of OGP are highly conserved between species (29) (Table S3), which agrees with the crossed action of porcine and bovine fluids, and (iii) OGP possesses heparin-binding consensus sequences (29) and heparin-binding sites (30), which would explain why heparin in the incubation medium stabilizes the hardening effect. To demonstrate the involvement of OGP in ZP modifications and its detachment in a medium lacking heparin, different experiments were performed.…”
Section: Oviduct-specific Glycoprotein Seems To Be Responsible For Thesupporting
confidence: 57%
“…cycle, (ii) nucleotide and amino acid sequences of OGP are highly conserved between species (29) (Table S3), which agrees with the crossed action of porcine and bovine fluids, and (iii) OGP possesses heparin-binding consensus sequences (29) and heparin-binding sites (30), which would explain why heparin in the incubation medium stabilizes the hardening effect. To demonstrate the involvement of OGP in ZP modifications and its detachment in a medium lacking heparin, different experiments were performed.…”
Section: Oviduct-specific Glycoprotein Seems To Be Responsible For Thesupporting
confidence: 57%
“…Unlike mice, the in vitro maturation (IVM) and fertilization (IVF) processes are the most common and economic choices for obtaining 2-cell embryos in a pig model. However, polyspermic fertilization is a major problem in porcine IVF [14]. To avoid the influences of the fertilization cone, which indicates the sperm entry position, and to prevent topological change of the two or more apposing pronuclei in the egg center caused by polyspermy after IVF, we chose porcine parthenogenetic embryos for use in the present study even though they may not represent normal embryonic development in the pig.…”
mentioning
confidence: 99%
“…In the future, gain-of-function experiments may help to confirm the importance of the Cterminal peptide of the rabbit oviductin in the development of early embryo. It was reported that oviductin has a function on fertilization [3], [4], [16], while our research suggested that oviductin also has a function on the release of early embryonic development block.…”
Section: Discussionmentioning
confidence: 45%
“…The homology comparisons also showed that there were 40-50% smilarities between rabbit oviductin and some enzymes of chitinase gene family, but the oviductins showed no chitinase activity [14]. In recent years, few researches concerning the roles of oviductins in the development of early embryo were reported [15], [16].…”
Section: Discussionmentioning
confidence: 92%